Pengaruh Perencanaan Pajak, Asimetri Informasi Dan Beban Pajak Tangguhan Terhadap Manajemen Laba - Aura Azzahra; Vita Aprilina (JRAK: Journal of Accounting Research and Computerized Accounting, 2024)
ABSTRACT The analysis here has a direction that shows the effect of tax planning, information asymmetry and deferred tax expense on earnings management in non-cycle consumer sector companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period. The method used in this analysis is quantitative method. The sample in this analysis uses purposive sampling method, where the population consists of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in the period 2020-2022. Based on the results of this analysis, it is found that tax planning has a positive impact on earnings management, while information asymmetry and deferred tax expense have no impact on earnings management. Keywords: tax planning, information asymmetry, deferred tax expense, earnings management